Biased preservation of Pleistocene climate variability proxies at Olduvai Gorge, Tanzania - Ferland, Troy M.; Colcord, Devon E.; Shilling, Andrea M.; Brassell, Simon C.; Stanistreet, Ian G.; Stollhofen, Harald; Njau, Jackson K.; Schick, Kathy D.; Toth, Nicholas; Freeman, Katherine H. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2021)
Olduvai Gorge in northern Tanzania contains a fossiliferous, well-characterized Pleistocene sedimentary record and provides the opportunity to study the relationships between a changing climate, ecology, and hominin evolution. The Olduvai Gorge Coring Project drilled four cores (1A, 2A, 3A, and 3B) into the depocenter of Paleolake Olduvai in 2014 to achieve increased temporal resolution of local climate and ecological data, and investigate the influence and timing of regional climate and tectonics on local signals. We present high-resolution records of bulk organic carbon isotopes (δ13Corg, ‰) from Cores 2A and 3A, total organic carbon (wt%) from Cores 2A and 3A, and organic carbon‑nitrogen ratios (C:N) from Core 2A. Previous work at Olduvai linked % TOC and δ13Corg to orbitally paced variations in lake depth and ecosystem dynamics from Upper Bed I and Lower Bed II (1.9–1.7 Ma), associated with eccentricity maxima and the presence of a perennial saline-alkaline lake in the basin. Bulk organic geochemical properties in both cores exhibit marked shifts in variance and magnitude at 1.9 and 1.7 Ma. Low % TOC values prior to and following 1.9–1.7 Ma implicate low productivity and/or increased degradation of organic matter, while C:N ratios from Core 2A reflect increased aquatic or bacterial input. Within the 1.9 to 1.7 Ma interval, high % TOC is dominated by terrestrial inputs as evidenced by high C:N ratios, and bulk δ13Corg captures high variability C3–C4 ecosystem dynamics. Climate variability is highest from 1.9–1.7 Ma, but the δ13Corg records are not consistent between Core 2A and Core 3A. From 1.9–1.7 Ma, Core 3A has increased indicators of erosion relative to Core 2A, suggesting a sedimentary aliasing of the δ13Corg record in Core 3A. Outside of the 1.9–1.7 Ma interval, both changes in organic carbon source and preferential preservation of proxies for wet conditions may obscure true climate variability, inviting further investigation into the ability of the Olduvai Gorge sedimentary record to test climate variability hypotheses for hominin evolutionary events.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Bulk organic carbon isotopes; East Africa; Mean-variance changepoint detection; Pleistocene climate